Evaluating the Vietnamese version of the book Chicken Soup for Mother and Daughter Soul" by Jack Candfield and Mark Victor Hasen using Julliane House's model - Nguyễn, Thị Bích Hạnh (University of Languages and International Studies, 2017)
The study aims at evaluating the English-Vietnamese translation of the book ‘Chicken Soup for Mother and Daughter Soul’ by Jack Canfield and Mark Victor Hansen using Julliane House’s model of translation quality assessment. In the study, basic concepts of (...)